Use of Palm Oil Mill Effluent (Pome) and Peat to Reduce Ammonia Volatilisation from Fertiliser Urea - Balasundram, Siva Kumar (1997)
Ammonia (NH3) volatilization is a major pathway of nitrogen loss which limits the efficiency of urea as a fertilizer when surface-applied to soils. High pH and low cation exchange capacity in soils have been identified as the principal causes ofNH3 volatilization from urea. The several approaches proposed to correct such inefficiency in urea, thus far, were fundamentally based upon delay of urea dissolution and impedance of urea hydrolysis. An attempt was made to establish a preferred environment within the urea-soil reaction zone (microsite) using palm oil mill efiluent (POME) and peat. Both POME and peat are organic matter-rich, and contain humic substances across their respective organic matrix. Humic substances have been shown to interact with ammoniacal compounds and urea. As such, a study was engaged to explore the effects of POME and peat, and their respective humic derivatives on NH3 volatilization from urea surface-applied to two Malaysian soils of contrasting pH values. The organic materials and their humic derivatives were separately matrixed with urea into pelletised form and evaluated under laboratory regimes for % NH3 volatilization, pH change and NHt + -N recovery. Estimation ofNH3 volatilization was carried out using a closed-dynamic air-flow system. Detennination of the chemical and physical attributes of soils and materials, and measurement of the parameters studied were done using standard procedures. Characterisation of the POME- and peat-derived humic substances was performed using chemical and spectral methods. Results showed that reduction in NH3 volatilisation by peat-treated urea was more pronounced than that of POME in both soils. Such reduction was accompanied by a corresponding increase in NH4+ recovery and decrease in pH particularly at the microsite. The use of differing matrixing ratios did not yield significant variation in the performance of matrixing agents. Acidification of POME and peat resulted in impedance of urea movement from micro site to outersite.